Measurement And Management Of Energy Usage In School Of Mechanical Engineering USM - Arbain, Azizi (Universiti Sains Malaysia, 2018)
As Malaysia moves towards the status of developed nation, the consumption of electrical energy has become an important role this day and has causes huge demand of building and electrical energy. Building sector is the major responsible for electrical energy utilization in Malaysia. Numbers of research and efforts have been done in order to cope with this problem. Energy saving policy is one of the campaigns done by the government as an initiative to reduce the energy consumption. This will eventually reduce the energy operating cost of an organization or building. However, most of the buildings used energy within the operation and maintenance stage. Therefore, measurement and management of energy usage is one approach that is being studied to reduce the energy consumption. In this project, the focus is on the energy usage of School of Mechanical Engineering, USM as school building has the highest electricity consumption among other schools building. Field work and inspection had been done and through energy audit, the cause and reason for high electricity consumption had been determined. Existing air conditioning system contributed 58% of total power consumption of school building. To overcome this problem, the current air conditioning system needs to be re-engineered. Inverter ait conditioning system should be used. Inverter air conditioning system varies the speed of the compressors, delivering precise cooling or heating required. Even it is more expensive than the existing ait conditioning system, an inverter air condition is at least 30%-50% cheaper to run as it consumes less power.